Air quality index pattern around petroleum production facilities - Sonibare, J.; Adebiyi, F.; Obanijesu, Emmanuel; Okelana, O. (Emerald Group Publishing Ltd, 2010)
Purpose: The aim of this paper is to better understand the impact of petroleum production facilities on ambient air quality of host airshed. Design/methodology/approach: Field measurements were taken daily for four consecutive months around petroleum production facilities in the Niger Delta area, of Nigeria, one of the world’s important petroleum producing areas. Statistical analysis tool and air quality analytical tool known as the air quality index (AQI) were applied on the field data obtained. Findings: The mean measured daily concentrations of both carbon monoxide (CO) and nitrogen dioxide (NO2) between distances 50 and 500 m of petroleum flow stations were of the range 140 – 3400 mg/m3 and 23 – 1250 µg/m3 respectively. The AQI from measured CO concentrations in the study area ranged between 1 and 44, an indication of good AQI category with no known health effects but a need for cautionary statement. Similarly, over 97 percent of the measured concentrations of NO2 were below 0.60 ppm which implies that the AQI of the host environment of the flow stations were below 200 with respect to NO2 thus indicating a good category of air with no health alarm. However, at the 60 m distance around a flow station, the AQI was 210 thus the quality of available air at this point could be described as very unhealthy. Generally the concentrations of CO were higher than NO2 in all the distances from the flow stations and were corroborated with their significant T-test values. The T-test results of the relationship between the concentrations of the air pollutants per time of the day, showed that their T-test values were not significant, indicating that concentrations of these air pollutants were independent of the sampling time. A strong and positive correlation existed between the two air pollutants signifying common sources.Originality/value: The paper highlights that at 60 m distance around petroleum production facilities, people with respiratory or heart disease, the elderly and children should be prevented from gaining access in the morning without taking necessary precautionary measures against the inhalation of air pollutants.